Implementing a Mentoring Program for Beginning Secondary STEM Teachers: Conceptualization and Lessons Learned - Smetana, Lara; Millsapp, Krishna; Leider, Megan; Johnson, Mark (Innovations in Science Teacher Education, 2023)
The importance of attending to teachers’ transition from student to teacher (i.e., induction period) is increasingly recognized. This article describes efforts to develop, implement, and iteratively revise a mentoring program for beginning secondary science and mathematics teachers. We explain the conceptualization of the program in terms of four dimensions of teachers’ professional practice and varying mentoring approaches and formats. Examples of mentoring program components illustrate the program design. Lessons learned from the first 2 years are explored utilizing participant data as evidence. Plans for our program are discussed as well as implications for other teacher education programs.